Sample size recalculation in three-stage clinical trials and its evaluation - Bokelmann, Björn; Rauch, Geraldine; Meis, Jan; Kieser, Meinhard; Herrmann, Carolin (BMC medical research methodology, 2024)
In clinical trials, the determination of an adequate sample size is a challenging task, mainly due to the uncertainty about the value of the effect size and nuisance parameters. One method to deal with this uncertainty is a sample size recalculation. Thereby, an interim analysis is performed based on which the sample size for the remaining trial is adapted. With few exceptions, previous literature has only examined the potential of recalculation in two-stage trials.